Viscosity characterization of confined bitumen considering microaggregate‐bitumen interactions. (5th May 2020) - Dong, Zejiao; Liu, Zhiyang; Yang, Chen; Gong, Xiangbing
Abstract: Microaggregate‐bitumen interactions in asphalt mixtures cause nonuniform rheological properties of bitumen adhering to aggregates. It is necessary to quantify microaggregate‐bitumen interactions so that the properties of the confined bitumen can be precisely characterized. This study developed a viscosity model of confined bitumen film considering microsubstrate–bitumen interactions. An exponential function was introduced to characterize the spatial distribution of viscosity under the effects of these microinteractions. The apparent viscosity of the bitumen film was formulated as an expression of thickness comprising bulk and interfacial viscosities and a decay index. The bulk viscosity showed a temperature dependence that corresponded with the Williams–Landel–Ferry model. The interfacial viscosity was higher than the bulk viscosity at high temperatures but lower at low temperatures, which indicates that the effect of substrate–bitumen interactions is bidirectional and depends on temperature. This phenomenon could be attributed to the microstructural transition of interfacial bitumen from an oriented layer to a disentangled one. Molecular dynamics simulations demonstrated the microstructural changes of interfacial bitumen under the effect of microaggregate‐bitumen interactions.